Coupling effect of ultrasonic vibration and beam oscillation on FQZ soften inhibition of laser welded Al-Mg alloy joints - Jiang Bi; Liukun Wu; Zeqi Liu; Haixiang Wang; Qian Li; Zhuoyun Yang (Materials Letters: X, 2023)
A novel ultrasonic vibration assisted laser beam oscillation welding (UV-LBOW) method was developed and applied on the butt-welding of Al-Mg alloy sheets. Due to the synergistic enhancement of the molten pool flow by ultrasound vibration and laser beam oscillation, the microstructure morphology of fusion zone (FZ) was comprised of equiaxed grains. Additionly, a uniform element distribution was generated from the boundary to the center of the FZ. An enhanced tensile strength of 347 MPa and a fraction elongation of 19.0 % were obtained due to the grain refinement and solid solution strengthening effects.